A query–matching mechanism over out–of–order event stream in IOT. (30th July 2013) - Wang, Kun; Yu, Yue
With the rapid development of Internet of Things (IOT) applications facing data stream and Complex Event Processing (CEP), the accuracy and effectiveness of query–matching are gaining increasing attention. Owing to the out–of–order event, the accuracy and speed of query–matching are degraded. Other problems are that current mechanism cannot properly support long query and buffer usage is low–efficient. To solve these problems, algorithms for generating and matching queries are proposed to raise accuracy in query–matching with relatively low overhead and shorten the response time as much as possible. Simulation shows that the proposed two algorithms are able to shorten response time and further improve matching accuracy over out–of–order event. Space complexity is also improved when the system is dealing with multiple queries.